Social media performance of user generated content and its relationship with conspicuous consumption: through the lens of the expectation confirmation theory - Ferreira, Caitlin (School of Management Studies, 2016)
Early theories of conspicuous consumption proposed a framework in which individuals attempt to imitate the consumption patterns of others that maintain a higher social status. This results in individuals ostentatiously displaying their consumption patterns in order to reinforce their social status. The advent of social media has provided individuals with a new platform on which to display their conspicuous consumption. All consumption now has the possibility to become conspicuous consumption, displayed to a large network of friends and followers online. When individuals post content on social networking sites (SNSs), referred to as user-generated content, they hold some initial expectations regarding the response that their content will receive. This response (for example Likes and Comments on Facebook) is referred to as Social Media Performance in the current research. While research has been conducted, albeit minimal research, into measuring the performance of brand-generated content, no academic research has considered the perceived performance evaluation of individual user-generated content. Previous research has identified a link between online performance, referred to as Social Media Performance in the current research, and conspicuous consumption. This link has however been suggested to be moderated by three variables, selfesteem, social media usage and emotion, tested separately as positive and negative affect. The current research sought to evaluate the moderating influences that selfesteem, social media usage and emotion exerted on the relationship between Social Media Performance and conspicuous consumption. This was done through the lens of the Expectation Confirmation Theory (ECT), as Social Media Performance is posited to follow an Expectation Confirmation Theory framework, in which SNS users are either satisfied or dissatisfied depending on their subjective evaluation of performance. A conclusive, causal research design was implemented; making use of a nonprobability sampling technique that achieved a sample size of 282 respondents. The target population consisted of young adults, between the ages of 18 and 29 years, due to the adoption of SNS usage amongst this age cohort. The results found a negative correlation to exist between self-esteem and conspicuous consumption and a positive correlation to exist between social media usage and conspicuous consumption. Furthermore, self-esteem, social media usage and negative affect were found to moderate the relationship between Social Media Performance and conspicuous consumption. In particular, in the presence of negative Social Media Performance, higher levels of social media usage and lower levels of negative affect exerted a greater influence on this relationship. Whereas in the presence of positive Social Media Performance, lower levels of self-esteem and higher levels of negative affect exert a greater influence on this relationship. This research has also confirmed the positive relationship between social media usage and conspicuous consumption.